2022
DOI: 10.7759/cureus.27245
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Amputation in Patients With Diabetic Foot Ulcers: A Systematic Review

Abstract: Foot ulcers are a leading cause of morbidity in diabetics. One of the known complications of diabetic foot ulcers is lower limb amputation which makes it a major socioeconomic problem. Currently, there's a lack of knowledge on the predictors of amputations in diabetics with foot ulcers. We performed a systematic review of studies that identified risk factors of amputation in patients with diabetic foot ulcers. This systematic review aims to identify the predictors of amputation in order to optimize the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Bigger, more homogeneous samples are mandatory for this examination and that would affect the significance and the level of confidence in some of the tested parameters, for example, body mass index and glycated haemoglobin. This was also emphasised in preceding studies that used a linked meta‐analysis technique and found equivalent values of the influence 58‐61 . Although the meta‐analysis was incapable to discover if differences in these characteristics are related to the outcomes being researched, properly‐led RCTs are vital to consider these aspects as well as the mixture of different ethnicities of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Bigger, more homogeneous samples are mandatory for this examination and that would affect the significance and the level of confidence in some of the tested parameters, for example, body mass index and glycated haemoglobin. This was also emphasised in preceding studies that used a linked meta‐analysis technique and found equivalent values of the influence 58‐61 . Although the meta‐analysis was incapable to discover if differences in these characteristics are related to the outcomes being researched, properly‐led RCTs are vital to consider these aspects as well as the mixture of different ethnicities of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Wagner grading was used to assess ulcer depth, osteomyelitis and necrosis/gangrene on a scale ranging from 0 to 5. Almost all DFU‐related amputation risk studies have highlighted the reliability of the Wagner classification in predicting amputation 16,17 . Because of the ulcer severity that increases with the Wagner classification grade, more extensive wounds often require amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results supported this finding, with an amputation rate of 50.1% ( n = 195) for forefoot ulcer (OR = 0.130, 95% CI = 0.061–0.277) and a median amputation‐free survival time of 4 months. PAD, a marker of atherosclerosis, has been widely discussed as an independent risk factor for DFU‐related amputation 17 . One study of cardiovascular disease risk factors found that the relative risk of cardiovascular death in patients with PAD was 1.69 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations